Comparison of Factors Associated with Nutritional Supplement Use and Non-Use Among Members of Fitness Centers in Tehran, Iran - Saeedi, Pouya (2012)
The aim of the first phase of this study was to determine the prevalence of nutritional supplement (NS) use among the members of the fitness center in Tehran, Iran. Twenty four fitness centers participated in this study. A questionnaire asking about socio-demographic characteristics and also supplement use in the previous six months of the study was used. Of 1625 fitness center members, aged 18 years old and above, a majority (66.7%) reported the use of NS in the previous six months of the study. Also, 0.5% of them used illegal substances (IS), and 11.2% reported the use of both NS and IS. The second phase of the study was an unmatched case-control study which aimed to determine the differences in socio-demographic factors, health-related factors, psychological factors and dietary intake between 147 nutritional supplement users and 147 non-users in fitness centers in Tehran, Iran. All data, except for dietary intake were collected using a self-administered questionnaire. The participants comprised 52.0% males and 48.0% females, with a mean age of 32.03 ± 11.40 years and 33.36 ± 11.23 years, respectively. More than half of the NS users (53.7%) were females and 46.3% were males, but among the non-users 42.2% were females and 57.8% were males. More than half of the NS users (55.1%) and 47.6% of non-users had bachelor/post graduate degree. A majority of the male and female NS users (66.2% and 50.6%, respectively) felt that it was “very important” to receive information about NS, whereas male and female non-users reported lower levels of importance. Creatine (63.2%) was a common NS among male users whereas iron tablets (50.6%) were common among female users. Exercise performance (54.4%) was the main reason for using NS among male users while maintaining health/preventing nutritional deficiencies (51.9%) was the main reason for female users. Multivariate logistic regression analysis showed that moderate (OR= 16.00, 95% CI=1.50-170.25) and high (OR= 16.73, 95% CI= 1.35-207.71) physical activity levels were the strongest predictors of NS use. Another strong predictor of NS use was sex,whereby NS users were more likely than non-users to be female (OR= 12.98, 95% CI= 4.59-36.71). Moreover, NS users were six times more likely than non-users to be at risk for eating disorders (OR= 6.60, 95% CI= 3.08-14.14). In addition, NS users were more likely than non-users to be smokers (OR= 3.65, 95% CI= 1.56-8.56).Furthermore, NS users were likely to be younger than non-users (OR= 2.11, 95% CI= 1.05-4.27). NS users were also two times more likely than non-users to perceive their current body weight as overweight/obese (OR= 2.39, 95% CI= 1.05-5.10). However, there was no significant difference in total energy, protein, carbohydrate and fat intakes between NS users and non-users. This study showed a high rate of NS use in this sample. Being female, being younger than 30 years old, having high levels of physical activity, being at risk of eating disorders and being smokers were associated with NS use. These results were consistent with other studies on NS use.